Retinal Involvement in COVID-19: Results From a Prospective Retina Screening Program in the Acute and Convalescent Phase - Bansal, Reema; Markan, Ashish; Gautam, Nitin; Guru, Rashmi Ranjan; Lakshmi, P. V. M.; Katoch, Deeksha; Agarwal, Aniruddha; Singh, Mini P.; Suri, Vikas; Mohindra, Ritin; Sahni, Neeru; Bhalla, Ashish; et al. (Frontiers in Medicine, 2021)
Objective: To detect retinal involvement in COVID-19 patients in acute and convalescent phase by their fundus screening. Methods: In a prospective, cross-sectional, observational study (July-November 2020), 235 patients (142 acute and 93 convalescent phase) underwent fundus screening in a tertiary care center in North India. For convalescent phase, ‘hospitalized’ patients (73) were screened at least 2 weeks after hospital discharge, and ‘home-isolated’ patients (20) were screened 17 days after symptom onset/COVID-19 testing. Results: None in acute phase showed any retinal lesion that could be attributed exclusively to COVID-19. Five (5.38%) patients in convalescent phase had cotton wool spots (CWS) with/without retinal hemorrhage, with no other retinal finding, and no visual symptoms, seen at a median of 30 days from COVID-19 diagnosis. Conclusions: CWS (and retinal hemorrhages) were an incidental finding in COVID-19, detected only in the convalescent phase. These patients were much older (median age 69 years) than the average age of our sample and had systemic comorbidities (diabetes mellitus, hypertension, etc.). We propose the term ‘COVID-19 retinopathy' to denote the presence of CWS at the posterior pole, occasionally associated with intraretinal hemorrhages, in the absence of ocular inflammation in patients with a history of COVID-19 disease.